Organizational communication through audiovisual equipment (2022)
Purpose of the following document is to present my experience as an intern in the academic department of the Foreign Languages Program at the University of Cartagena and the challenges I faced in the different activities I had to perform. Likewise, I will describe a problem that I was able to evidence during my stay in the academic department, why I identify it as a problem and I will also highlight viable solutions to improve or mitigate said problem and strengthen the national and international image of the professional university program in Foreign Languages of the UDeC.